University lecturers’ insights in asynchronous training: A moodle-based national professional development program - Hendriana, Benny; Apoko, Tri Wintolo; Hanif, Isa Faqihuddin; Irdalisa; Fatayan, Arum; Handayani, Isnaini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study explores university lecturers’ perceptions of a national professional development program delivered asynchronously via the Moodle platform in Indonesia. While asynchronous learning is increasingly adopted for large-scale training, limited research has examined how lecturers in developing countries perceive its usability, effectiveness, and challenges. Addressing this gap, the study aimed to investigate lecturers’ perceptions and the challenges they encountered during Moodle-based asynchronous training. Using a mixed-methods approach with a sequential explanatory design, this study involved 511 Indonesian lecturers selected through total population sampling for the quantitative phase and purposive sampling for the qualitative interviews. The questionnaire as the quantitative instrument measured four sub-scales: accessibility, ease of use, effectiveness, and motivational impact of LMS. The questionnaire demonstrated strong reliability (Cronbach’s Alpha = 0.877). Descriptive statistical analysis was employed, revealing high mean scores for all aspects (M = 4.65 to 4.85), indicating positive perceptions of the training. The highest agreement was found in the ease of implementing the training via the LMS (M = 4.85, SD = 0.39). Qualitative data were collected through semi-structured interviews and analysed thematically, highlighting challenges such as unstable internet access, limited device functionality, and unclear material organization. These results suggest that while Moodle is perceived as an effective tool for professional development, structural and technical improvements are needed. The study recommends enhanced technical support, better content structuring, and training orientation to increase engagement and learning outcomes in similar future programs.